Viscosity and surface tension of saturated toluene from surface light scattering (SLS) - Fröba, Andreas Paul; Leipertz, Alfred (International Journal of Thermophysics, 2001)
It is demonstrated that dynamic light scattering (DLS) on a horizontal gas-liquid interface can be used for the reliable determination of surface tension and liquid kinematic viscosity. In contrast to the more usual approaches of surface light scattering (SLS) spectroscopy, a setup is used and described here which makes it possible to measure the capillary wave propagation characteristics in the forward scattering direction at variable wave numbers. The experiments in this work rely on a heterodyne detection scheme and signal analysis by photon correlation spectroscopy (PCS). Surface tension and liquid viscosity data of the important and, thus, well-documented reference fluid toluene have been measured under saturation conditions over a wide temperature range, from 263 to 383 K. These data demonstrate the excellent performance of the surface light scattering technique. The achievable accuracy of this technique is discussed in detail for both properties in connection with reference values available in the literature.
Keywords: dynamic light scattering; surface light scattering; surface tension; toluene; viscosity